Mewaspadai Pembajakan Operasi Perdamaian: Telaah Kritis Intervensi Asing dalam Konflik Libya - Nuruddin Al Akbar (Institute of International Studies, 2015)
This study seeks to explore the hidden challenges to the mission/operation of peace (peace operation/mission). Ideally, as envisioned by the perspective of liberal peace, humanitarian mission should be carried out purely on the basis of values of humanism in order to address the humanitarian crisis phenomenon. However, this assumption has weaknesses because it is ignorant of potential piracy against peace operations in which the latter are just cover for the implementation of the vested interests of the actors involved in the mission. Piracy against peace operations is essentially a new form of